PHILOSOPHICAL FOUNDATIONS AND ETHICS: A DECONSTRUCTION AND RECONSTRUCTION OF KENYAN EDUCATION SYSTEM - Mwanzia, Ruth M.; Njoki, Wane; Muthaa, George (Machakos University, 2019)
One of the objectives of education is to promote ethical behaviour among learners. This is emphasized by various commissions and reports on education. Despite the enormous investment in education over the years and the high academic qualification, the level of impunity, corruption and intolerance among graduates and other leavers has become a major concern among educationists and stakeholders. Efforts through reforms and commissions have not yielded much in developing ethics among learners. This raises concern on the influence of contemporary philosophical foundations on ethics. The current study aimed at determining the influence of deconstruction and reconstruction of Kenyan philosophical foundations on ethics among learners in all levels of education. The study was carried out in Kenyan universities and communities. Descriptive survey and correlation research design were adopted for the study. A sample size of 384 respondents comprising of 324 students and 60 academic staff participated in the study. Data collection was done using questionnaires and interviews. Instrument validity was enhanced through expert judgement by supervisors. Reliability of instruments was estimated by use of Cronbach Alpha. Descriptive statistics and inferential statistics were used to analyze the data. Research hypothesis was tested using regression and correlation analysis at a significance level of α = 0.05. The study found out that the contemporary philosophical foundations and reconstructed philosophical foundations contribute significantly towards ethics. The null hypothesis that there exists no significant influence on deconstruction and reconstruction of philosophical foundations on ethics is not supported in the current study. The study recommends the need to deconstruct and reconstruct the contemporary philosophical foundations in order to influence ethics among learners in all the levels of education
Keywords: Deconstruction; Reconstruction; Contemporary; Philosophical foundations; Ethics